The role of education in economic growth: theory, history and current returns (2013)
The paper examines the role of education in economic growth from a theoretical and historic perspective, addresses why education has been the limiting factor determining growth, discusses why certain countries have provided education to the masses and others have not, provides estimates of the quantitative importance of the direct and the indirect effects of education on the economy, calculates the marginal national return on investment for 60 countries, and examines the implications of these results for government policy.